Qurʾanic Reception in Kitāb Maulid al-Barzanji: Exegetical, Aesthetic, and Functional Modes of Meaning Transformation - Ruspan Hamdani; Akhmad Supriadi; Nor Faridatunnisa (Universitas Islam Negeri Imam Bonjol Padang, 2026)
Kitāb Maulid al-Barzanji, composed by Jaʿfar al-Barzanji in the 12th century AH/18th century CE, holds a central position in Muslim devotional life across the Malay-Indonesian world. While existing scholarship has examined its liturgical and cultural significance, its Qurʾanic dimension, particularly the presence, reception, and transformation of Qurʾanic verses within its narrative structure, remains underexplored. This study investigates the modes of Qurʾanic reception embedded in Maulid al-Barzanji, focusing on the identification of Qurʾanic verses thematically aligned with its faṣl narratives and their reinterpretation within hagiographical, cosmological, and panegyric discourses. Employing a qualitative library-based methodology, this research utilizes systematic content analysis through keyword identification, semantic mapping, and cross-referencing with two authoritative exegetical works: Tafsīr Mafātīḥ al-Ghayb by Fakhr al-Dīn al-Rāzī and Tafsīr al-Munīr by Wahbah al-Zuḥaylī. The analytical framework draws on Ahmad Rafiq's theory of Qurʾanic reception, categorizing reception into exegetical, aesthetic, and functional modes. The findings reveal strong thematic correspondences between selected Qurʾanic verses, including Q.S. al-Anbiyāʾ [21]:107, Q.S. al-Qalam [68]:4, Q.S. al-Aḥzāb [33]:21, and Q.S. al-Isrāʾ [17]:1, and narrative episodes concerning the Prophet's birth, moral excellence, exemplary conduct, and spiritual journey. These verses function exegetically as theological legitimations, aesthetically through symbolic and literary elaboration, and functionally as normative references shaping ritual practice and communal identity. The study argues that Maulid al-Barzanji represents a form of living tafsīr (al-tafsīr al-ḥayy), wherein Qurʾanic meanings are dynamically rearticulated into devotional narratives. This research thereby contributes to Living Qurʾan studies by demonstrating how Qurʾanic reception operates through hagiographical literary constructions that reinforce prophetic authority and collective religious experience.